SPATIOTEMPORAL LAND USE AND LAND COVER CHANGE IN MAJOR RIVER BASINS IN COMPREHENSIVE DEVELOPMENT AREA - Wan Ibrahim, Wan Yusryzal; Muhamad Ludin, Ahmad Nazri (PLANNING MALAYSIA, 2016)
Urbanization has significantly transformed spatial configuration of landscape structure which is triggered by population growth and government’s development policy. As a consequence, the changes disturbed the quality of natural environment and ecosystem. Historical experience and prediction of future land use and land cover change is important to understand the spatial characteristics and environmental consequences of development area. Evaluating the spatiotemporal in urban development is essential as an important component improving adaptive management in landscape planning. Thus, the objective of this paper is to discuss the spatiotemporal land use and land cover change in major river basins (Sungai Tebrau, Sungai Skudai, Sungai Pulai and Coastal Zone) in the rapid development region of Iskandar Malaysia. The past experience indicates rapid growth of population and substantial urban development changed the spatial structure of the region and there is tremendous transformation of land use and land cover in the present due to high demand for development. Analytical Hierarchical Process (AHP) and CA-markov chain model were used to analyze the relationship of variables and formulate the future spatial changes. Then landscape index is used to analyze the spatial characteristics of the changes. Remote sensing data and GIS were used to conduct the analysis for the study. Temporal satellite images between 2002 and 2013 were utilized as input data for the past changes and basis for future land use and land cover change projection (2020, 2025 and 2025). The result indicates different character of urban landscape changes in different periods and river basins. Past experience shows the significant change of agricultural and natural land converted into artificial land use especially in Skudai and Tebrau river basins. In addition, there was conversion of water body for development in the past especially along the river banks and coastal area in Johor Bahru city center. This trend will constantly restructure the existing landscape as projection shows the significant impact of future development. This situation could contribute to other possible issues such as microclimate change and increase run-off water, pollution and degradation of ecological values and services. This study provides a platform for decision-makers to interpret the situation of landscape structure change in relation with environmental consequence in the study area. Future development plan should thoroughly consider the character of future spatial development and anticipate the possible effect on the environment in the region.